Des temples et des quartiers disparus en Chine - Adeline Herrou (Ateliers d'Anthropologie)
Recent changes undergone by several (Quanzhen) Daoist temples in Central China, caused by a major-works policy, take on a special meaning if considered in light of the aftermath of the profound break that had already marked the religious landscape during the Cultural Revolution (1966-1976). Placing the two highly contrasting periods in perspective has led me to the troubling observation that after the disappearance of the temples and the efforts made to resurrect them, nearby districts have often ended up destroyed. Neighbouring communities that uphold the memory of the temples and bring them alive find themselves being dismantled. This article takes as its anthropological subjects these destructions of villages or urban districts, and the upheavals they cause in the life of the society. It is based on long-term ethnographic fieldwork, whose heuristic value will be shown in order to understand not only the meaning that is locally attributed to these tabula rasa phenomena, but also how everyone’s zero point of observation (including that of the ethnologist) determines their perception of the event. Finally, it shows that the principle of “the offering in return for the granted wish” establishes a direct relationship between donations—used to periodically embellish and enlarge the temples—and the ritual effectiveness ascribed to those holy places.